Implementation Of Academic Information Systems In Improving The Quality Of Academic Services In Private Islamic Higher Educations - Tanjung, Rahman; Wasliman, Iim; Saeful Insan, Husen; H. Soro, Suharyanto (Lafadz Jaya Publisher, 2022)
The background of this research is that there has not been a habit of using academic information systems by both lecturers and students, there are no educational staff from the field of computer science or informatics, and the limited budget they have. This research approach is a qualitative research with case study method. The results of this study indicate that academic information system planning refers to the blue print for the development, management and utilization of higher education information systems. The organization assigns a direct assistant to the Head of Academic and Student Affairs who is assisted by two operators, whose operational direction is based on a decree issued by the leadership which is fully managed by the Telecommunications Center. Coordination of academic information systems based on the participation and support of all parties. Control is carried out directly by the Chairman as the leader. The obstacles faced in general are that there is no budget available considering the need for the development of an Academic Information System that requires a large amount of money, the age of most of the lecturers is old so it is quite difficult to adapt to changes towards digital and the ability of lecturers to use information systems is still low. The solution is to encourage students and lecturers to want to get used to adapting and learning in the use of academic information systems